LAYANAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN SOLIDARITAS PESERTA DIDIK KELAS VIII DI SMPN 21 PONTIANAK - Noviani, Rizka; Wicaksono, Luhur; Yusuf, Abas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractIn friendship is very influential on teen self â€“ image. Teenagers get closer to their peers. Because they assume that friends in their desires so they want to consercrate their time with their friends. Teenagers in hanging out with peers feel given status and gain sympathy. The problem in this study is â€œgroup guidance services to increase the solidarity of class VIII grade students in SMPN 21 Pontianakâ€. The method used is descriptive method and the form of the research is a suvey study. The population in this study were 37 students in SMPN 21 Pontianak. The study uses a quantitative approach. Collection tool with questionnaire while data analysis uses a percentage formula. Based on the results of this study indicate that group guidance services to improve the most dominant solidarity are the first, second, and fourth stages of the â€œgoodâ€ category. Obtained the correlation coefficient number rs=0,334. In can be concluded that in this study indicates a correlation in can be concluded that in this study â€œ there is effectiveness in group guidance services to improve the solidarity of class VIII in SMPN 21 Potianakâ€.Â Keywords: Group Guidances Services, Solidarity